The Effect of Work-Life Balance and Work Environment on Job Satisfaction with Work Stress as a Mediating Variable at the Class I Immigration Office of TPI Padang - Syafira Aviola; Rahmi Fahmy; Hendra Lukito (International Journal Labs, 2022)
Background: The Covid-19 virus attack has had a great impact on human life in the world and has changed many important aspects of life such as health, the economy, politics, and also security. It has also led to changes in working methods and also human interaction within the organization. As one of the agencies affected by the Covid-19 virus, namely the Class I Immigration Office of TPI Padang. Since the Covid-19 virus pandemic, many changes have occurred and various efforts have been made within the Class I Immigration Office of TPI Padang to break the chain of the spread of the Covid-19 virus, one of which is by working from home for ASN. Objective: This study aims to examine and build a conceptual model of the effect of work-life balance and work environment mediated by work stress on job satisfaction in ASN employees. Methods: This study used a non-probability sampling technique with the sample used being 72 civil servants through the distribution of questionnaires. Results: This study found that work trends do not mediate the effect between work-life balance and work environment on job satisfaction in employees of the Class I Immigration Office of TPI Padang. Conclusion: The Class I Immigration Office of TPI Padang has provided appropriate working hours so that the personal life and working life of employees can be balanced and the existing work environment of the TPI Padang Class I Immigration Office provides a sense of security and comfort to employees. With a sense of security and a sense of comfort at work, employee job satisfaction will increase.